Decomposition of Political Reality through Arthur Asa Berger's Humor Strategy: A Pragmatic Study in Indonesian Stand-up Comedian - Elsara Khairun Nisa; Rustono; Tommi Yuniawan; Rahayu Pristiwati (JPI: Jurnal Pustaka Indonesia, 2026)
Political discourse in Indonesia is currently expanding from the formal sphere to the popular stage through stand-up comedy . This study aims to dissect the mechanism of political reality decomposition through Arthur Asa Berger's humor strategy to reveal political criticism communicated pragmatically. Using a qualitative descriptive design, this study analyzed primary data sources in the form of speeches by stand-up comedians Ridwan Remin, Pandji Pragiwaksono, and Akbar obtained purposively from YouTube channels. Data analysis was conducted using a pragmatic decomposition technique that refers to Berger's four categories of humor techniques: language, logic, identity, and action. The results show that humor strategies operate as instruments of power desacralization. In terms of identity, ideal attributes of leaders are decomposed into trivial labels (caricatures); in terms of language, puns are used to satirize collective corruption; in terms of logic, analogies are used to simplify systemic failures; and in terms of action, visual parodies reduce political rhetoric to ridiculous movements. The conclusion of this study confirms that pragmatic decomposition in stand-up comedy functions as a tool of social control that reduces the complexity of power into a satirical, educational, and critical narrative for society.